Foreground-background: investigating trajectory of smell in navigating architectural space - Ruth Kartika Purnasasmita,; Yandi Andri Yatmo, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study investigates the trajectory of smell in space as the basis of architectural design methods development. It began with the discussion that architecture often removes or overwrites the presence of smell based on its stimulating existence created from matter. In this study, the experience of smell is considered in the form of trajectory. This study highlights that—instead of understanding smell as one fixed occurrence in space— understanding smell through the idea of trajectories enables dynamic navigation of boundaries and movement in space. This investigation of the trajectory of smell could reveal layers of smell in space. These layers can be seen in the form of foreground-background compositions. This study investigates smell by conducting the process of smellwalking in the context of Mayestik, a local public market in South Jakarta to reveal such trajectories. In this study, the trajectories of smell are constructed by the smell’s movement (the distribution of smell in space), human movement, and the existing layers within the space. The layers and trajectories of smell play a role as olfactory cues in navigating space, highlighting the dynamics and fragmentary characters of smell that are then translated into various acts of bodily responses. These findings suggest possible architectural programming operations based on the layers and trajectories of smell, considering the transactional relations between smell, the surrounding environment, and human movement.